Studi Komparatif Pembentukan Portofolio Optimal dalam Pengambilan Keputusan Investasi - Ni Made Erawati; I Nengah Suarmanayasa (Universitas Pendidikan Ganesha, 2021)
This study aims to compare the optimal portfolio formation method using a single index model and stochastic dominance in determining investment decisions. There are three aspects that are compared, namely portfolio return, portfolio risk and portfolio performance which are analyzed using the performance measurement ratios of Sharpe, Treynor, and Jensen. The sample used in this study was 31 consistent company stocks included in the LQ45 index from 2016 to 2019. Mann Whitney U test was used to test the research hypothesis. The results showed that (1) there was a significant difference in portfolio expectation returns using the single index model and stochastic dominance methods, (2) there was no significant difference in portfolio risk using the single index model method with stochastic dominance, (3) there was no significant difference. portfolio performance (Sharpe ratio) uses the single index model method with stochastic dominance, (4) there is no significant difference in portfolio performance (Treynor ratio) using the single index model method with stochastic dominance, (5) there is a significant difference in portfolio performance (Jensen's ratio) using the single index model method with stochastic dominance.